Bentuk Fisik Angklung Sebagai Perwujudan Kosmologi dan Makna Sosial - Salley Anwary Sumadi, Roly; Triharini, Meirina (Program Studi Pendidikan Musik, 2024)
Angklung, a traditional musical instrument from West Java, Indonesia, has undergone significant development in various aspects. This study examines the evolution of angklung in terms of its physical form, musical application, and socio-cultural significance. The research employs a literature review method by collecting data from relevant sources. Findings revealed that socio-culturally, angklung has not only maintained its relevance but also gained increasing popularity and appreciation, both domestically and internationally. The study concludes that angklung, as a traditional artistic artifact, continuously evolves and adapts to the times without losing its cultural essence.